(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
Inhibition of the inflammatory response through bark polyphenolics can help to downregulate the effects of chronic inflammation and related conditions. This study mainly investigates the polyphenolic properties and their corresponding bioactivities of Vitex altissima L.f. bark. The extracts assessed for their yield percentage, secondary metabolites, and anti-inflammatory properties of V.altissima were determined using the protein denaturation method. Through in silico modeling, it confirms the binding affinity of compounds from GC-MS analysis to the inflammation protein. The results indicated that Thalavadi-III’s V.altissima recorded the highest phenolic content on 48.23 mg GAE/g extract, while Mundathurai-I exhibited the highest flavonoid content at 25.8 mg RE/g extract. Anti-inflammation properties showed the highest percentage of inhibition in Iggalore’ V.altissima . To add more significance, the compounds from GC-MS analyses were predetermined by in silico docking analyses [benzenamine, 4,4’-[sulfonylbis(4,1-phenyleneoxy)]bis- (-6.73); hematoporphyrin (-6.22)] against inflammation protein, which confirmed